Analisis Tindak Tutur Ilokusi pada Teks Debat dalam Buku Bahasa Indonesia Kelas X Kurikulum 2013 - Yumna Aqilah; Maulidia Rahmania Anandi; Nova Alfitri; Vania Nasywa Ulayya; Ayu Hastutik Munadziroh; Dewi Rahmah Salsabila; Asep Purwo Yudi Utomo (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
In the context of debate, another issue that occurs is the limited skills of students in identifying and formulating appropriate illocutionary speech acts. In a debate, it is important to communicate arguments clearly and convincingly. However, learners who do not understand the pragmatic aspects of language may have difficulty in formulating strong arguments. This study was conducted to determine the illocutionary speech acts contained in the debate text of Indonesian language book class X curriculum 2013. The purpose of this research is to examine the application of illocutionary speech acts in debate texts. The method used in this research is descriptive qualitative analysis, pragmatics theoretical approach, and data collection techniques with observational studies on Indonesian language book documents grade X curriculum 2013. The analysis technique used in the research uses agic analyzing technique. This research makes a significant contribution to understanding and improving the application of illocutionary speech acts in debate texts. The results of this research, there is some data that covers the aspects of illocutionary speech acts in debate texts. The data contains expressive, directive, assertive, declarative, and commissive illocutionary speech act categories totaling 34 data. It is concluded that the application of illocutionary speech acts can be identified and classified in speech acts that are adjusted to the category. The benefit of this research is as a source of knowledge to deepen the science of pragmatics in illocutionary speech acts.